Discovery of a potent and selective ROMK inhibitor with improved pharmacokinetic properties based on an octahydropyrazino[2, 1-c][1, 4]oxazine scaffold. Issue 23 (1st December 2016) - Zhu, Yuping; de Jesus, Reynalda K.; Tang, Haifeng; Walsh, Shawn P.; Jiang, Jinlong; Gu, Xin; Teumelsan, Nardos; Shahripour, Aurash; Pio, Barbara; Ding, Fa-Xiang; Ha, Sookhee; Priest, Birgit T.; et al.
Graphical abstract: Abstract: Following the discovery of small molecule acyl piperazine ROMK inhibitors, the acyl octahydropyrazino[2, 1-c][1, 4]oxazine series was identified. This series displays improved ROMK/hERG selectivity, and as a consequence, the resulting ROMK inhibitors do not evoke QTc prolongation in an in vivo cardiovascular dog model. Further efforts in this series led to the discovery of analogs with improved pharmacokinetic profiles. This new series also retained comparable ROMK potency compared to earlier leads.